(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The functioning of the forestry complex in Russia is currently associated with many systemic problems and is complicated by the current economic situation in the country. The purpose of this article is to reveal the main systemic problems of the Russian timber industry complex existing at the present stage of development, to consider possible ways and strategies for solving these problems. To solve these problems, it is necessary to develop modern resource-saving technologies, introduce new technology and equipment to obtain new generation goods from woodworking waste, ensure a more complete development of forest resources, conduct active innovation, attract investments, train qualified personnel, and an effective policy in the field of protection. and conservation of forests.